2020
DOI: 10.33225/pec/20.78.167
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Students’ Arithmetic Skills of Teaching Two Differently Structured Calculation Methods

Abstract: Mastering traditional algorithms has formed mathematics teaching in primary education. Educational reforms have emphasized variation and creativity in teaching and using computational strategies. These changes have recently been criticized for lack of empirical support. This research examines the effect of teaching two differently structured written calculation methods on teaching arithmetic skills (addition) in grade 2 in Sweden with respect to students' procedural, conceptual and factual knowledge. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…During these periods, students exercised mental arithmetic with the AI Engine three times per week, each training session lasting ten minutes. The interventions replicated a research design from a study that concluded that even short arithmetic training with non-adaptive software or with pen and paper substantially improved students' general performance in mathematics (Engvall et al, 2020). Both interventions included pre-, peri-and post-tests of students' skills.…”
Section: Observations and Interviewsmentioning
confidence: 79%
“…During these periods, students exercised mental arithmetic with the AI Engine three times per week, each training session lasting ten minutes. The interventions replicated a research design from a study that concluded that even short arithmetic training with non-adaptive software or with pen and paper substantially improved students' general performance in mathematics (Engvall et al, 2020). Both interventions included pre-, peri-and post-tests of students' skills.…”
Section: Observations and Interviewsmentioning
confidence: 79%
“…It helps students develop logical thinking and problem-solving abilities (Björklund, 2021). Thus, arithmetic is an essential component of the primary mathematics curriculum (Engvall et al, 2020). Baroody and Dowker (2003), Dowker (2005), Geary (1993), Goldman and Hasselbring (1997), Hiebert and Lefevre (1986), and Kilpatrick et al (2001) carried out research on how students attain arithmetic proficiency.…”
Section: Introductionmentioning
confidence: 99%